REGULASI PEMBIAYAAN KESEHATAN: DAMPAK EKONOMI TERHADAP KUALITAS LAYANAN MEDIS - Violla Evarista; Singgih Purnomo; Andhika Rahmadi Putra (Proceedings Law, Accounting, Business, Economics and Language, 2025)
This article discusses health financing regulations as an important foundation in determining the quality of medical services in Indonesia, especially amid economic challenges and regional disparities in access. This study aims to analyze in depth the impact of financing regulations on the quality of health services using a descriptive qualitative approach. The findings indicate that the effectiveness of regulations remains limited in ensuring equitable access, efficient allocation of funds, and operational sustainability of healthcare facilities, especially in remote areas. Delays in fund disbursement, weak financial management at the local level, and insufficient oversight are the main obstacles to policy implementation. Additionally, an unstable financing system imposes additional burdens on medical staff and lowers service standards. Therefore, improvement strategies should focus on strengthening financial information systems, harmonizing central and local policies, and implementing performance incentives that encourage service quality improvement. Through comprehensive and collaborative improvements, health financing regulations can become an effective tool in achieving fair, quality, and sustainable medical services.